FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TANI BAWANG DAUN (Allium fistulosum L) (STUDI KASUS DI KECAMATAN BERGAS KABUPATEN SEMARANG) - Agung Prasetyo (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Spring onion was a type of food plant that has long been known and cultivated in developing countries. Bergas District, Semarang Regency, has an area that makes scallions a leading agricultural sector. This study aimed to determine the factors that affect the income of leek farming. The method of determining the location used was purposive with simple random sampling for Collecting samples. Data analysis using OLS with the Cobb Douglas function. The results showed that the factors of land area, labor, seeds, and manure had a significant effect on the income of leek farmers. More efforts are needed to innovate and have the courage to cultivate leeks not only with an intercropping system so that income from farming can be higher.